Characterization of a novel alternatively-spliced 5′ exon in the human insulin-like growth factor I (IGF-I) gene, expressed in liver and some cancers. (June 2019) - Wallis, Michael
Abstract: In mammals, the large IGF-I gene comprises 6 exons, which are subject to alternative splicing. All transcripts contain exons 3 and 4, encoding mature IGF-I, but the other exons are included in various combinations, giving at least 6 possible mature mRNAs. At the 5′ end, exons 1 and 2 are spliced alternatively to exon 3, giving different leader/signal sequences. It is shown in this study that in human an additional exon (designated exon 0) is present, upstream of exon 1. This can be spliced directly to exon 3 or, less frequently, into exon 1. Exon 0 is utilized in liver, in about 24% of IGF-I transcripts, to a minor extent in prostate and endometrium (<1% of transcripts), but not in any of 29 other normal human tissues examined. The exon 0 sequence includes an in-frame ATG/AUG, potentially providing a translation start point giving an IGF-I precursor with a very long signal peptide. However, this ATG is very close to the 5′ end, and may not be included in all transcripts; an in-frame ATG in exon 3 could provide an alternative start point. Utilization of exon 0 was detected in other apes, and to a small extent in Old World monkeys, but not in New World monkeys, prosimians or various non-primate mammals. Exon 0 was not expressed in most human tumours, but was utilized in many prostate tumours, at levels much greater than seen in normal prostate, and in liver tumours, at a lower level than in normal liver. Highlights: A novel alternatively-spliced exon (exon 0) occurs at the 5′ end of human IGF-I gene. Exon 0 could encode a 65-aa signal peptide, or be an untranslated leader sequence. Exon 0 is expressed in liver ( 24% of all 5′ splices), but <1% in other tissues. Significant utilization of exon 0 is found only in human and apes, not other mammals Exon 0 is expressed in many prostate tumours.